Hydrogel delivery of DNase I and liposomal vancomycin to eradicate fracture-related methicillin-resistant staphylococcus aureus infection and support osteoporotic fracture healing - Li, Jie; Leung, Sharon Shui Yee; Chung, Yik Lok; Chow, Simon Kwoon Ho; Alt, Volker; Rupp, Markus; Brochhausen, Christoph; Chui, Chun Sing; Ip, Margaret; Cheung, Wing-Hoi; Wong, Ronald Man Yeung (Acta biomaterialia, 2023)
Fracture-related infection (FRI) is a devastating complication in orthopedic surgery. A recent study showed that FRI causes more severe infection and further delays healing in osteoporotic bone. Moreover, bacterial biofilm formed on implants cannot be eradicated by systemic antibiotics, warranting novel treatments. Here, we developed a DNase I and Vancomycin hydrogel delivery vehicle to eradicate Methicillin-resistant Staphylococcus aureus (MRSA) infection in vivo. Vancomycin was encapsulated in liposomes, and DNase I and Vancomycin/liposomal-Vancomycin was loaded on thermosensitive hydrogel. In vitro drug release test showed a burst release of DNase I (77.2%) within 72 h and sustained release of Vancomycin (82.6%) up to day 14. The in vivo efficacy was evaluated in a clinically relevant ovariectomy (OVX) induced osteoporotic metaphyseal fracture model with MRSA infection, and a total of 120 Sprague Dawley rats were used. In the OVX with infection group, biofilm development caused a drastic inflammatory response, trabecular bone destruction, and non-union. In the DNase I and Vancomycin co-delivery hydrogel group (OVX-Inf-DVG), bacteria on bone and implant were eradicated. X-ray and micro-CT showed preservation of trabecular bone and bone union. HE staining showed the absence of inflammatory necrosis, and fracture healing was restored. The local elevation of TNF-α and IL-6 and increased number of osteoclasts were prevented in the OVX-Inf-DVG group. Our findings suggest that dual release of DNase I and Vancomycin initially followed by Vancomycin only later up to 14 days effectively eliminates MRSA infection, prevents biofilm development and provides a sterile environment to promote fracture healing in osteoporotic bone with FRI. - Statement of significance - The biofilm on implants are difficult to eradicate, causing recurrent infection and non-union in fracture-related infection (FRI). Here we developed a hydrogel therapy with high in vivo efficacy to eliminate MRSA biofilm infection in a clinically-relevant FRI model in osteoporotic bone. By loading DNase I and vancomycin/liposomal-vancomycin on thermosensitive poly-(DL-lactic acidco-glycolic acid) (PLGA)-polyethylene glycol (PEG)-PLGA hydrogel, a dual release of DNase I and Vancomycin was achieved whilst preserving enzyme activity. In this model, the progressive development of infection caused a drastic inflammatory response, osteoclastogenesis, trabecular bone destruction, and non-union of fracture. These pathological changes were successfully prevented by the dual delivery of DNase I and vancomycin. Our findings provide a promising strategy for FRI in osteoporotic bone.